English Teachers’ Personally-Initiated Learning (PIL): Their Professional Development Preferences - I.G.A. Lokita Purnamika Utami (Soegijapranata Catholic University, 2019)
This article aims at reporting a result of a small research in Bali about English teachers’ personally-initiated learning (PIL) preferences. The study was done through a small survey involving 156 English teachers and continued with a focus group discussion (FGD). The survey was mainly about English teacher’s PIL preferences, and the aspects which influence their participation. The survey revealed some PIL preferences, namely: web-browsing, reading books, colleagues sharing, reflection from experience and doing research. Following the survey analysis, 2 times of 90 minutes FGD were conducted by involving 15 English teachers. The focus group discussion was conducted to see English teachers’ PIL experiences and opinion regarding the PIL preferences found in the survey. The study found that English teachers’ preferences were influenced by their time, family responsibility, ability, age, effect-relevance and school-culture. Besides that, personal motivation was found to be essential in their professional development participation. Suggestions for school administrators are discussed as it reflects the implication of the findings of the study.